HUBUNGAN PEMBERIAN ASI EKSKLUSIF DAN VITAMIN A DENGAN KEJADIAN PNEUMONIA PADA BALITA DI KELURAHAN KIBING WILAYAH KERJA PUSKESMAS BATU AJI KOTA BATAM TAHUN 2022 - Hutapea, Misda Shinta; Roza, Nelli; Hayat, Nahrul (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2023)
Pneumonia is responsible for nearly 20 percent of these deaths and is the leading cause of death from infectious diseases for the under-five age group. Based on the Profil Kesehatan Indonesia (2022), pneumonia is still a major problem causing 73.9% of deaths. Pneumonia in Batam City received 4,762 toddlers, and the highest data was obtained in the Kibing sub-district of 175 cases in the working area of ​​the Batu Aji Health Center, Batam City. One of the factors that cause pneumonia is exclusive breastfeeding and low vitamin A. This research aims to see the relationship between exclusive breastfeeding and vitamin A with the incidence of pneumonia in toddlers in the Kibing subdistrict, Batu Aji Health Center Working Area, Batam City in 2022. This research is an analytical study with a cross sectional design. To 62 respondents with a sampling technique with cluster random sampling technique. The results of the chi-square statistical test were obtained (p = 0.005 <0.05), meaning that there was a significant relationship between exclusive breastfeeding and the incidence of pneumonia, in Vitamin A (p = 0.003 <0.05), meaning that there was a significant relationship between vitamin A and pneumoniae. The head of the Batu Aji Health Center is expected to be able to create a work program by increasing IEC for exclusive breastfeeding of infants and vitamin A to toddlers.